Creativity Under Disclosure: How AI Disclosure Labels Shape Consumers’ Perceptions of Advertising Creativity - Senkler,Ole; Staudinger,Helena (2026)
The increasing use of generative artificial intelligence (GenAI) in advertising has transformed creative production while simultaneously raising concerns about transparency, authenticity and consumer perception. With the growing integration of GenAI into advertising, understanding how consumers respond to AI disclosure has become increasingly important. This study investigates how AI disclosure in advertising influences consumers’ perceptions of creativity and examines whether originality, appropriateness and skepticism mediate this relationship. Drawing on the Persuasion Knowledge Model, algorithmic aversion theory and advertising creativity literature, a quantitative online survey using a between-subject experimental design was conducted. Participants were randomly assigned to either an AI disclosure or no-disclosure condition while evaluating the same advertisement. Data were analyzed using independent samples t-tests and mediation analyses. The findings show that AI disclosure significantly reduces advertising creativity. Advertisements labeled as AI-generated were evaluated as less creative than identical advertisements without disclosure. The results further demonstrate that this effect is primarily driven by lower perceptions of originality and appropriateness. While AI disclosure slightly increased skepticism, skepticism did not significantly mediate the relationship between disclosure and creativity. This study contributes to the growing literature on AI-generated advertising by positioning perceived creativity as a central outcome variable in AI disclosure contexts. The findings further highlight the challenges marketers face in balancing transparency requirements with maintaining the creative impact of advertising campaigns.
Keywords: Artificial Intelligence (AI); AI disclosure; AI in advertisements; advertising creativity; algorithmic aversion; Persuasion Knowledge Model (PKM)